Analisis Laporan Keuangan Dalam Mengukur Kinerja Keuangan BAZNAS Provinsi Sumatera Barat Periode 2020-2022 - Siti Ramadhani; Eka Septiana; Fadillah Dwi Sintawati; Alia Rahmawati (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
The aim of this research is to analyze and measure the financial performance of the National Amil Zakat Agency (BAZNAS) in West Sumatra Province from 2020 to 2022. This study uses the strategic study center of BAZNAS to calculate activity ratios, efficiency ratios, amil fund ratios, and growth ratios. Quantitative data from the financial reports of BAZNAS in West Sumatra Province for the years 2020–2022 are used. In this research, data were collected through observation and documentation using descriptive quantitative techniques. As a result of the activity ratio analysis, BAZNAS in West Sumatra Province is considered quite effective in the distribution and collection of Zakat, Infaq, and Sedekah (ZIS) funds. While the operating cost ratio to amil rights and the operating cost ratio to total amil rights are inefficient, the efficiency ratio also shows fairly efficient results. However, the collection ratio, human resource cost ratio, and amil fund ratio show good results. Meanwhile, the growth ratio shows less favorable results, with both the collection and distribution growth ratios showing suboptimal outcomes.